Self-calibrating floating-point analog-to-digital converter - Debski, Michal (University of Ottawa (Canada), 2005)
The Floating-Point Analog-to-Digital Converter (FPADC) is an extended version of the Fixed-Point ADC. It is designed to deal with a broader dynamic range of signals while exhibiting a smaller relative quantization error. The traditional implementation of the FPADC is characterized by a high relative precision, but it requires high-precision high-speed components in order to achieve that. The high precision of the high-speed components comes at a greater cost. This constraint limits the availability of FPADCs to high-priced designs. The thesis addresses a low-speed and a low-cost calibration approach for the FPADC. It presents the architecture, design and implementation platform of a self-calibrating differential predictive FPADC which is characterized by utilizing low-grade components. The precision is maintained at high values by additional hardware that periodically performs calibration cycles. Starting with a review of the field of FPADC the thesis develops the understanding of the Floating Point ADCs. The implementation is then extended to include a high precision low speed calibrating ADC. A complete implementation of the design is carried out and described. Finally, experimental measurements are performed to test the new FPADC and present the acquired results.
Keywords: Engineering, Electronics and Electrical.